Codigestão anaeróbia de resíduos hortifruti, efluente de fecularia e efluente de indústria de processamento de sangue animal - Ferreira, Elves dos Santos (2023)
The search for energy is a tireless objective for human beings, since traditional energy resources are finite. Anaerobic biodigestion, in addition to providing biomass treatment, can be a source of renewable energy, since the production of gas with a high methane content has a high calorific value. Considering the complexity of anaerobic monodigestion of fruit and vegetable waste, due to its high concentrations of sugars, co-digestion brings the nutritional balance necessary to carry out the process. Therefore, the aim of this work was to evaluate the anaerobic co-digestion of horticultural waste (RHTF) with effluent from the animal blood processing industry (ESBS) and starch factory effluent (EF), seeking the ideal proportion of waste mixture for greater efficiency. anaerobic process. The substrates were collected and the tests were carried out in the municipality of Mundo Novo, Mato Grosso do Sul. Simplexlattice mixture planning was used with 10 experimental tests and the definition of the mixture planning matrix was based on the analyzes physicochemical characteristics of each substrate. The anaerobic codigestion process lasted 16 days, with an abrupt drop in pH observed at the beginning of the process. The use of anaerobic co-digestion provided a maximum COD removal of 93% and an average volatile solids removal of 50.88%. A biogas with a high calorific value was observed, with the majority of tests having a variation in CH4 content from 58 to 94%. The use of mixture planning proved to be effective for the use of several components, however, due to data variability, it was not possible to obtain a valid model that explains the process. An alternative to reduce variability and find an optimal point is to carry out tests on the mixture planning matrix with repetitions.